Civic freedom in an age of diversity : the public philosophy of James Tully - Karmis, Dimitrios; Maclure, Jocelyn, 1973- (Democracy, diversity, and citizen engagement series, 2023)
"James Tully is one of the world's most influential political philosophers at work today. Over the past thirty years--first with Strange Multiplicity (1995), and more fully with Public Philosophy in a New Key (2008) and On Global Citizenship (2014)--Tully has developed a distinctive approach to the study of political philosophy, democracy, and active citizenship for a deeply diverse world and a de-imperializing age. Civic Freedom in an Age of Diversity explores, elucidates, and questions Tully's innovative approach, methods and concepts, providing both a critical assessment of Tully's public philosophy and an exemplification of the type of dialogues of reciprocal elucidation that are central to Tully's approach. Since the role of public philosophy is to address public affairs, the contributors consider public philosophy in the context of pressing issues and recent civic struggles such as: crises of democracy and citizenship in the Western world; global citizenship; civil disobedience and non-violence; Indigenous self-determination; nationalism and federalism in multinational states; protest movements in Turkey and Quebec; supranational belonging in the European Union; struggles over equity in academia; and environmental decontamination, decolonization, and cultural restoration in Akwesasne. Offering a wide-ranging analytical discussion of James Tully's work by leading scholars from various fields of study, with an extensive reply by Tully himself, Civic Freedom in an Age of Diversity provides a rich perspective on the full extent of Tully's contribution."--